PENDAMPINGAN KELOMPOK BELAJAR MANDIRI “FKIP UNIVERSITAS PEKALONGAN MENGAJAR” UNTUK REMAJA USIA SEKOLAH (SMP DAN SMA) - Dwi Ario Fajar; Erwan Kustriyono; Amalia Fitri (LPPM Universitas Pekalongan, 2021)
The characteristics of children's behavior in the millennial era are marked by a strong mastery of digital media, so how do parents determine parenting to build a generation that does not accept the bad effects of the digital era, but uses all media wisely and for positive purposes. Family education is an effort to empower families to be able to exercise control over existing resources and active participation in character formation. The condition of the Covid-19 pandemic has forced families to be more attentive to the process of their children participating in their learning activities at school. Many families in Bandengan Village have difficulty guiding their children in learning activities, especially learning assistance during the Covid-19 pandemic. The majority of the people of Bandengan Village earn as casual laborers, small fishermen and factory workers. By implementing the FKIP Mengajar and mentoring program for independent study groups in Bandengan Village, it is hoped that it can help the people of Bandengan Village in the field of education, especially the problem of learning difficulties experienced by teenagers. The method used in this service is active participation and mentoring. This strategy can be summarized as follows: 1. Grouping of Adolescents according to School Age 2. Learning Assistance (school materials, Multi Literacy, and general skills,) 3. Formation of Independent Study Group 4. Independent learning group mentoring. The synergy between universities and the community is needed in a real form. FKIP Pekalongan University provides solutions to problems in the learning assistance of parents for their children. Independent learning group mentoring is a tangible form of solving learning mentoring problems in the community.Keywords : independent learning, family education, mentoring.